Growth of human immunodeficiency virus-uninfected children exposed to perinatal zidovudine for the prevention of mother-to-child human immunodeficiency virus transmission - Nelly Briand (2018)
Background: Perinatal human immunodeficiency virus (HIV) prevention programs have been implemented in several countries, and many children have been or will be exposed to antiretrovirals in utero and during their first weeks of life. Although reducing substantially the number of infected children, the potential adverse consequences of these treatments on the health of HIV-uninfected children need to be assessed. Objective: To investigate the impact of in utero and postnatal zidovudine exposure on the growth of HIV-uninfected children born to HIV-infected women. Methods: We used data prospectively collected in 1408 live born children participating in a clinical trial comparing zidovudine regimens of different durations to prevent perinatal transmission in Thailand (PHPT-I). We used a linear mixed model to analyze the anthropometric measurements (weight for age, height for age and weight for height Z-scores) until 18 months of age according to zidovudine treatment duration (mothers, <7.5 weeks versus more; infants, 3 days versus >4 weeks). Results: Children exposed in utero for >7.5 weeks had a slightly lower birth weight (Z-score difference, 0.08; P = 0.003). However, zidovudine exposure had no effect on the evolution of Z-scores from 6 weeks to 18 months of age. Conclusions: Although a longer in utero zidovudine exposure may have had a negative impact on birth weight, the magnitude of this effect was small and faded over time. Neither the total nor the postnatal duration of exposure was associated with changes in infant Z-scores from 6 weeks to 18 months of age. Copyright © 2006 by Lippincott Williams & Wilkins.